Augmented reality, for the teaching-learning process of the chemistry course at the secondary level in the schools of Lambayeque - Vargas Zatta, Felipe Alejandro (2023)
The objective of this study is to optimize the teaching-learning process of the chemistry course at the secondary level in schools in Lambayeque through the use of augmented reality software. This study consisted of applying augmented reality software developed by myself, creating and using cards with augmented reality objects. In this software, students can take their chemistry course class and view each object on the sheet through the application. The evaluation of the software was carried out with the participation of 40 students from the 4th year of high school, each of them using a cell phone. A survey in the form of a questionnaire was used to evaluate the level of approval of the use of augmented reality software, which consisted of a Likert scale with five levels. Students completed these questionnaires to provide feedback and opinion on the usefulness and effectiveness of the software. As a result of this research, it can be concluded that the augmented reality software demonstrated good performance in detecting markers and displaying 3D objects.